2010
DOI: 10.2174/1874120701004010077
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Failure Properties of the Porcine Medial Collateral Ligament-Bone Complex for Predicting Injury in Automotive Collisions

Abstract: The goal of this study was to model the dynamic failure properties of ligaments and their attachment sites to facilitate the development of more realistic dynamic finite element models of the human lower extremities for use in automotive collision simulations. Porcine medial collateral ligaments were chosen as a test model due to their similarities in size and geometry with human ligaments. Each porcine medial collateral ligament-bone complex (n = 12) was held in a custom test fixture placed in a drop tower to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
(23 reference statements)
2
1
0
Order By: Relevance
“…The high-load mechanical properties (failure deformation, failure strain, stiffness, and modulus) of porcine MCL were comparable to adult human MCL (Tables 3 and 4). Similar to our study of immature porcine MCL, Peck (2007) found that the majority of their mature porcine MCLs failed by tibial avulsion. Failure loads (703 7232 N) and stresses (65716 MPa) of mature porcine MCLs (Peck, 2007) were comparable to those obtained with our protocol (Tables 3 and 4).…”
Section: Speciessupporting
confidence: 88%
See 2 more Smart Citations
“…The high-load mechanical properties (failure deformation, failure strain, stiffness, and modulus) of porcine MCL were comparable to adult human MCL (Tables 3 and 4). Similar to our study of immature porcine MCL, Peck (2007) found that the majority of their mature porcine MCLs failed by tibial avulsion. Failure loads (703 7232 N) and stresses (65716 MPa) of mature porcine MCLs (Peck, 2007) were comparable to those obtained with our protocol (Tables 3 and 4).…”
Section: Speciessupporting
confidence: 88%
“…Porcine MCL was assumed to have a rectangular cross-section and XSA was calculated from midsubstance width and thickness measurements. In the one other study that examined biomechanical properties of domestic pig MCLs, (Peck, 2007), the author indicated that they also used a rectangular assumption and found that mature porcine MCL XSA ranged from 6.1-20.1 mm 2 , which was similar to our findings of 8.8À 19.5 mm 2 for immature porcine MCLs. The high-load mechanical properties (failure deformation, failure strain, stiffness, and modulus) of porcine MCL were comparable to adult human MCL (Tables 3 and 4).…”
Section: Speciessupporting
confidence: 86%
See 1 more Smart Citation